Dehydroxylative Trifluoromethylthiolation, Trifluoromethylation, and Difluoromethylation of Alcohols. Issue 2 (25th December 2019) - Zhang, Wei; Lin, Jin‐Hong; Wu, Wenfeng; Cao, Yu‐Cai; Xiao, Ji‐Chang
Summary of main observation and conclusion: CF3 S, CF3 and HCF2 groups have been identified as valuable functionalities for drug development. Despite significant accomplishments in the trifluoromethylthiolation, trifluoromethylation and difluoromethylation reactions, directly converting common functional groups into CF3 S, CF3 or HCF2 groups is still highly desirable. Described here is the dehydroxylative trifluoromethylthiolation, trifluoromethylation and difluoromethylation of alcohols promoted by a R3 P/ICH2 CH2 I system. All of these dehydroxylative reactions were achieved under mild conditions via the activation of the hydroxyl group by the R3 P/ICH2 CH2 I system. A wide substrate scope and good functional group tolerance were observed. Abstract : Dehydroxylative trifluoromethylthiolation, trifluoromethylation and difluoromethylation of alcohols were achieved under mild conditions via the activation of the hydroxyl group by a R3 P/ICH2 CH2 I system.